Efficacy of Dupilumab in two patients with severe and recalcitrant atopic dermatitis previously treated with extracorporeal photopheresis. Issue 3 (2nd March 2020) - Russo, Filomena; Taddeucci, Paolo; Lazzeri, Laura; Flori, Maria L.; Rubegni, Pietro
Abstract: Atopic dermatitis (AD) is a complex disease and can often be a clinical challenge for dermatologists. When standard immunosuppressive therapies fail, extracorporeal phototherapy (ECP) can be considered as a therapeutic option. In recent years, better understanding of the pathogenesis of AD allowed to improve treatment strategies with many emerging therapeutic options. Currently, Dupilumab, a monoclonal antibody that selectively inhibits IL‐4 and IL‐13, is the only biological drug authorized for the treatment of severe adult atopic dermatitis, refractory to traditional firstline and secondline therapies. ECP, compared to biological therapy, is associated with some disadvantages: it is costly and time‐consuming for patients and personnel to administer. Moreover, it should be noted that the completion of the entire procedure takes about 3 hr and must be done in a hospital, while the administration of Dupilumab can be carried out by patients themselves at home. For these reasons and on the basis of our experience, it would be necessary to evaluate whether all patients with refractory atopic dermatitis in treatment with ECP with unsatisfactory clinical response should be switched to recent available target therapies.